Selective Whole Blood Lipoprotein Apheresis to Prevent Pancreatitis in Drug Refractory Hypertriglyceridemia - Hovland, Anders; Hardersen, Randolf; Mollnes, Tom Eirik; Lappegård, Knut Tore (JOP. Journal of the Pancreas, 2010)
Context Severe hypertriglyceridemia is a known cause of acute pancreatitis, and apheresis treatment, most commonly plasmapheresis, has been used to treat patients with drug refractory hypetriglyceridemia for more than 30 years. Case report We report a case in which a woman with Crohn’s disease and type 2 diabetes mellitus developed recurrent episodes of acute pancreatitis due to extreme hypertriglyceridemia. After the initiation of lipoprotein apheresis from whole blood, a marked reduction of triglyceride and lipoprotein levels was observed. Some inflammatory parameters were increased even if most of the cytokines were not detectable, indicating good biocompatibility of the filter. Conclusions Triglyceride levels were lowered after initiating selective lipoprotein apheresis. More importantly, the patient did not experience any relapses of pancreatitis after the treatment was started. Hence this treatment is feasible in drug refractory hypertiglyceridemia, but the treatment concept needs to be tested in additional studies. Image: Average levels of triglycerides.